BIODIVERSITY OF HOME GARDEN EDIBLE PLANTS IN TEPUS, BLIMBING, AND SUMBEREJO, SEWUREJO VILLAGE, MOJOGEDANG, KARANGANYAR, CENTRAL JAVA - Agustin, Mariska Rosida; Andrianto, Roi; Rosyida, Syarifah Hasna (Jurnal Review Pendidikan dan Pengajaran, 2024)
Indonesia has various types of flora and fauna spread throughout its territory. This great potential can also be seen from the diversity of edible plants that thrive in various regions. This biodiversity plays an important role in supporting food security, health, and ecosystem sustainability. This study aims to determine the biodiversity of edible plants in home yards in Tepus, Blimbing, and Sumberejo Hamlets, Sewurejo Village, which is important to know the local potential in supporting food security and preserving the biodiversity of the region. The research method used is a qualitative method with community interviews as the primary data source used and analyzed using the Use Value (UV) formula, Relative frequency of citation (RFC), and Index of Cultural Significance (ICS). The results of the study found 50 species from 27 families. The most common plants came from the Fabaceae family, such as Parkia speciosa Hassk., Vigna unguiculata (L.) Walp, and Archidendron pauciflorum and others. The highest UV value was obtained by Cocos nucifera L. species, which was 0.038. The highest RCF value is Mangifera indica L. (0.305). And Cocos nucifera L. and Manihot esculenta Crantz plants have the highest value on the ICS index (42).